Dynamic performance of a Skystream wind turbine: A bond graph approach. Issue 1 (1st January 2019) - Gonzalez-A, Gilberto; Barrera-G, Noe; Ayala, Gerardo; Aaron Padilla, J.; Alvarado-Z, David
Abstract: The modelling in bond graph of a Skystream wind turbine composed by the blades, a permanent magnet synchronous generator (PMSG), three-phase rectifier, Boost converter and an inverter which is classified as a small-scale system is presented. Bond graphs permit to model systems formed by different energy domains. The Skystream turbine is a good case study to show that the bond graph model is presented in a unified representation approach. The electric power generation system based on this turbine is three-phase, the use of multibond graphs to model the PMSG, three-phase rectifier and inverter are proposed. However, the blades and Boost converter are modelled by single bond graphs. The mathematical representation of a section of a blade and the PMSG are obtained. In order to validate the simulation results obtained by bond graph models, an experimental study of the Skystream is compared with the complete simulation of the turbine. The motivation to develop these models in a bond graph approach is to design and build a low-cost wind turbine similar to the Skystream. Thus, the main contributions of this paper are: a bond graph model of the Skystream wind turbine, the PMSG, rectifier and inverter is modelled by multibond graphs.